Justice Endures Forever: Paul's Grammar of Generosity - Eubank, Nathan (Journal for the study of Paul and his letters, 2015)
For centuries before and after Paul, Jewish sages taught that charitable deeds are among the supreme acts of fidelity to God. Paul himself taught what might be called a traditional Jewish theology of charitable giving. He describes generosity to humans as an act of service for God that will bring happy returns in the future. He uses the cultic and financial metaphors that are common in other Jewish discussions of charity, and he also quotes biblical texts that speak of God's protection of the generous. This article concludes by noting the implications of this largely unrecognized point of continuity between Paul, Jesus, and the prior biblical tradition for situating the collection on the larger landscape of Paul's theology and for understanding how Paul develops his understanding of charity in light of the Christ.